HEPATITIS C VIRUS TRANSMISSION RISK FACTORS - Rathore, Javed Akhtar; Shah, Masood Alam; Mehraj, Adnan (Journal of Ayub Medical College Abbottabad, 2012)
Background: Hepatitis C Virus (HCV) is major health hazard. About 350 million people have been suffering from HCV infection in the world. HCV progresses into chronic liver disease in 50- 80% of cases and may end up in cirrhosis. This study was carried out to explore the transmission of risk factors for HCV. Methods: This prospective study included 210 consecutive HCV patients of either sex, ranging from 20-69 years of age, referred to Sheikh Khalifa Bin Zyad Hospital/ Combined Military Hospital, Muzaffarabad, Azad Kashmir. In patients having HCV positive by ELISA, the PCR qualitative tests of HCV RNA were performed. A questionnaire was filled for every patient regarding possible risk factors. Results: Most common risk factors among HCV patients were surgical procedures (p<0.001), followed by injections (p<0.05), dental surgeries (p<0.010), ear and nose piercing (p<0.001), and shaving (p<0.001). Univariate analysis identified tattooing (p=0.033) also as an important risk factor. Conclusion: Multiple risk factors have been identified in nearly all HCV infected patients. The identification of multiple risk factors of hepatitis C acquisition may have important implications in the approach to HCV surveillance, prevention, and management. Keywords: Hepatitis C virus, Polymerase chain reaction, PCR, Risk Factors